2021
DOI: 10.1177/20503121211014073
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D regulation of the immune system and its implications for COVID-19: A mini review

Abstract: The novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is at the origin of the current pandemic, predominantly manifests with severe respiratory symptoms and a heightened immune response. One characteristic of SARS-CoV-2 is its capacity to induce cytokine storm leading to acute respiratory distress syndrome. Consequently, agents with the ability to regulate the immune response, such as vitamin D, could become tools either for the prevention or the attenuation of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 60 publications
0
59
0
1
Order By: Relevance
“…While SARS-CoV-2 stimulates the release of proinflammatory cytokines, vitamin D inhibits the release of some of these molecules ( 31 ). Furthermore, vitamin D is known to regulate different thrombotic pathways, either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…While SARS-CoV-2 stimulates the release of proinflammatory cytokines, vitamin D inhibits the release of some of these molecules ( 31 ). Furthermore, vitamin D is known to regulate different thrombotic pathways, either directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…11 There is substantial variation between individuals in the immune response to vaccination. Vitamin D enhances epithelial integrity and induces antimicrobial peptide (eg, cathelicidin) synthesis in epithelial cells and macrophages 12,13 directly enhancing host defence., The effect of vitamin D on immune system has been recognized, 14 at a cellular and molecular level, They mainly targets helper T cell activity (Th1) by inhibiting the secretion of both IL-2 and IFN-gamma and by suppressing the secretion pro-Th1 cytokine IL-12 by antigen-presenting cells. 15 With the emergence of relatively vaccine-resistant SARS-CoV-2 variants, characterising the speed and duration of response to COVID-19 vaccines in iron deficiency, hypovitaminosis D is necessary to measure the expected benefits of the vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the UK-Biobank showed that although circulating vitamin D levels did not affect the risk of COVID-19 infection, the habitual use of vitamin D supplements was significantly associated with a 34% lower risk of COVID-19 infection (p = 0.034) [12]. Notably, vitamin D plays a physiologic role in regulating normal innate and adaptive immunity [13], and it has been reportedly shown to be able to suppress pro-inflammatory and stimulate anti-inflammatory cytokine formation, which might have a positive impact on COVID-19 patients [13,14]. In this scenario, COVID-19 pandemic has placed under the spotlight the correlation among IL-6, cytokine release syndrome, hyperinflammation state and COVID-19 fatality rate [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis is that there might be a strict correlation between vitamin D status and IL-6 serum levels. Nonetheless, albeit a role of vitamin D has been proposed in counteracting COVID-19 [3,4,13,14] through the potential modulation of the immune dysfunction and cytokine storm, to date, there is still a lack of evidence in the literature in terms of differences in serum levels across large cohorts, according to disease status.…”
Section: Introductionmentioning
confidence: 99%